Cancer and COVID-19: Unmasking their ties. (August 2020) - Addeo, A.; Friedlaender, A.
Highlights: The COVID-19 pandemic has reshaped health-care systems worldwide. Roughly 20% of patients develop complications and 3–6% die from COVID-19. Patients with malignancy are more susceptible to severe infection and mortality from COVID-19. Metastatic lung cancer and haematological cancer patients appear to be at greatest risk of severe complications and mortality from COVID-19. There may be biological overlap between the inflammation caused by immune-related pneumonitis, chimeric antigen receptor T-cell cytokine release syndrome and COVID-19 pneumonitis. Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) and its clinical manifestation, the coronavirus disease 2019 (COVID19) have rapidly spread across the globe, leading to the declaration of a pandemic. While most present mild symptoms, it appears as though nearly 20% of confirmed patients develop significant complications. These include acute respiratory distress syndrome, septic shock and multi-organ failure, with a 3–6% mortality. A plethora of treatments has been or is being assessed, but to date, none has been proven effective. Management is mainly symptomatic, with organ support for the critically ill. Several reports, mainly case series, from across the world have concluded that patients with malignancy appear more susceptible to severe infection and mortality from COVID-19. This could be attributed to immunosuppression, co-existing medical conditions and underlying pulmonary compromise which is often the case in lung malignancy. Patients with haematological cancer and those who are receiving active chemotherapy treatment may be at greatest risk due to increased immunosuppression. This pandemic tested the resilience of worldwide health-care systems in an unprecedented manner. It has forced oncologists to rethink the entire diagnostic and therapeutic process, based on the local prevalence and impact of COVID-19. In this review we will discuss the impact of COVID-19 on patients affected by cancer, their diagnosis and management, as well as the pathophysiology of COVID-19 induced acute respiratory distress symptoms and currently investigated treatment approaches.